Problemy wdrożeniowe strategii - Sołoducho-Pelc, Letycja (The Main Strategy Implemenation Problems, 2008)
This paper reveals that implementation is not a single decision or action but a type of actives over a long period of time. Strategy implementation literature identifies the main inhibitors of failure and successful strategy implementation and deliberates the most important tool for strategy implementation - Balanced Scorecard (BSC).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 332-339